2018
DOI: 10.3390/molecules23030579
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal Saponins from Vernonia amygdalina Del. and Their Biological Activity

Abstract: In the present study, four new steroidal saponins, namely vernoniamyoside A–D (1–4), together with the two known steroidal saponins vernoamyoside D (5) and vernonioside B2 (6) were isolated from the ethanol extract of leaves of the African medicinal plant Vernonia amygdalina Del. (Asteraceae). Their structures were demonstrated by spectral analyses along with 1D and 2D nuclear magnetic resonance (NMR) techniques and mass spectrometry (MS). The cytotoxicity of the compounds was also tested by the 3-(4,5-dimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…Free radicals are unstable molecules that cause oxidative stress, triggering cell damage, antioxidants are substances that may prevent or delay cell deterioration, vegetables and fruits are a rich source of antioxidants (Lobo et al, 2010). The percentage of free radical scavenging activity was found to be significantly low, which may be due to a lower concentration of phenol (Wang et al, 2018) and flavonoids in the present study (Liu et al, 2018). Lin et al (2016) observed mild antioxidant activity in the essential oil of A. chinense bulb which supports the present findings.…”
Section: Antioxidant Assaysupporting
confidence: 85%
“…Free radicals are unstable molecules that cause oxidative stress, triggering cell damage, antioxidants are substances that may prevent or delay cell deterioration, vegetables and fruits are a rich source of antioxidants (Lobo et al, 2010). The percentage of free radical scavenging activity was found to be significantly low, which may be due to a lower concentration of phenol (Wang et al, 2018) and flavonoids in the present study (Liu et al, 2018). Lin et al (2016) observed mild antioxidant activity in the essential oil of A. chinense bulb which supports the present findings.…”
Section: Antioxidant Assaysupporting
confidence: 85%
“…They are mainly distributed among monocotyledonous families: Amarillidaceae (Agapanthus, Allium), Asparagaceae (Agave, Anemarrhena, Asparagus, Convallaria, Hosta, Nolina, Ophiopogon, Ornithogalum, Polygonatum, Ruscus, Sansevieria, Tupistra, Yucca), Costaceae (Costus), Dioscoreaceae (Dioscorea), Liliaceae (Fritillaria, Lilium), Melanthiaceae (Paris), Smilacaceae (Smilax). Although it is uncommon, steroidal saponins can also be found in some dicotyledonous angiosperms, such as: Fabaceae (Trigonella), Zygophyllaceae (Tribulus, Zygophyllum), Solanaceae (Solanum, Lycopersicon, Capsicum), Asteraceae (Vernonia), and Plantaginaceae (Digitalis) (Faizal and Geelen 2013;Rahman et al 2017;Lanzotti 2005;Sobolewska et al 2016;Tang et al 2013;Wang et al 2018). Moreover, these compounds have been identified in starfish and marine sponges (Ivanchina et al 2011; Barnett et al 1988;Regaldo et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…foam. The Venoniamyosides family was characterized by the peaks at 1456, 1507 (C=C aromatic stretching), 1771 (unsaturated aliphatic ester and carbonyl C=O) and 3392 cm -1 (OH groups) (Wang, Song et al 2018). The intensity ratio of foam and initial extracts at these peaks (1456, 1507, 1771 and 3392 cm -1 ) were 1.6, 2.1, 1.8 and 2.2, respectively.…”
Section: Identification Of V Amygdalina Extracted Substances By Ftirmentioning
confidence: 99%
“…The resolution setting was 2 cm -1 . The peaks detection was based on reported vibronic FTIR peaks assignments (Tawata, Taira et al 1996, Gao, Ci et al 2000, Shao, Guo et al 2007, Abbas, Compère et al 2017, Tambe, Patil et al 2017, Wang, Song et al 2018).…”
Section: Ftir Analysis Of Extractmentioning
confidence: 99%
See 1 more Smart Citation